Analisa Pemasangan Dinding Bata Ringan Sesuai AHSP Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat Tahun 2022 dan 2023 pada Pembangunan Gedung Instalasi Perawatan Intensif Terpadu (IPIT) RSUD dr. R. Koesma Tuban - Erwin Andriyani; Sugeng Hartantyo; Yosef Cahyo (Jurnal Talenta Sipil, 2026)
Significant changes in labor coefficients and material coefficients in the AHSP 'installation of 1m2 of 10 cm thick lightweight brick wall with ready-mixed mortar.' The purpose of this study is to test the AHSP from the years 2016, 2022, and 2023 of lightweight brick installations with a thickness of 10 cm using ready-mixed mortar, as well as to compare the HSPK of lightweight brick with kumbung brick based on the results of the construction study of the IPIT RSUD dr. R. Koesma Tuban building. The research method uses a comparison of labor and material coefficients with a productivity method. The analysis results show that the labor and material coefficients approach the AHSP based on the Minister of PUPR Regulation No. 8 of 2023, which is: workers (1:1.03), craftsmen (1:1.73), foremen (1:1.07), lightweight bricks (1:0.95), mortar (1:1.01), and HSPK (1:1.04). The analysis of the unit cost of masonry using 10 cm thick lightweight bricks with ready-mix mortar is lower compared to the unit cost of masonry using hollow bricks with a thickness of half a brick mixed at 1PC : 4 PS based on SNI DT 91-0009-2007, resulting in a comparison of 1 : 1.21, with a total difference obtained from the IPIT project at RSUD dr. R. Koesma Tuban amounting to Rp123,254,569.84 or 17.66% of the total masonry budget. It can be concluded that the coefficients in the unit cost guidelines for lightweight brick masonry in accordance with the Minister of PUPR Regulation No. 8 of 2023 can be implemented in construction projects, which is consistent with the removal of the unit cost guidelines for hollow brick masonry from the unit cost guidelines in Minister of PUPR Regulation No. 8 of 2023.